Constraints Faced in Functioning of Self Help Groups by the Members under Rajasthan Condition - Ganga Devi, D.K. Jain (Indian Journal of Extension Education, 2022)
The discussion on socio-economic impact of self-help groups (SHGs) on its beneficiaries revealed somemajor problems faced by the members in functioning of SHGs. Main constraints faced by the members were found to be lack of finance and lack of marketing facility in economic constraints category; lack of infrastructure and lack of knowledge of loan procedure in technical constraints category; and lack of education and mutual understanding in the social constraints category, respectively